PENGEMBANGAN MODUL PEMBELAJARAN FISIKA BERBASIS LEARNING CYCLE UNTUK SISWA SMP KELAS VIII - Resviorita, Resviorita; Trisoni, Ridwal; Haris, Venny (Jurnal Pembelajaran MIPA, 2014)
The aim of this research was to develop physics learning module gets basis learning cycle for material effort, style and energy to class VIII valids one and practical at SMPN 3 Pariangan. This research utilize development research( research development ). This research comprise of four phases which is: pendefenisians phase, scheme phase,developmental phase and broadcast phase. But in this research just utilized by pendefenisians phase, scheme phase and development phase. On pendefenisians phase activity that doing to cover interview by learns SMPN 3 Pariangan, menganalisis is semester learning syllabus two, menganalisis is semester physics textbook two VIII classes and meriviuw is literatures about module. On scheme phase is done design of physics learning module gets basis learning cycle. On activities developmental phase which performing to cover phase validates physics learning module get basis learning cycle and research instrument, praktikalitas is physics learning module gets basis learning cycle. Of research result that is done at class VIII to point out that: Module gets basis learning cycle one that is designed was really valid (covering loading validity and konstruk) of expert viewpoint (validator), and was practical looked of learning module purpose physics gets basis learning cycle in estimation physics learning observer and student.Key words : development, module , physics learning, learning cycle